PRMT1-Dependent Macrophage IL-6 Production Is Required for Alcohol-Induced HCC Progression - Zhao, Jie (Gene Expr, 2019)
Alcohol is a well-established risk factor for hepatocellular carcinoma, but the mechanisms are not well understood. Several studies suggested that alcohol promotes tumor growth by altering immune cell phenotypes in the liver. Arginine methylation is a common posttranslational modification generated mostly by a single protein, PRMT1. In myeloid cells PRMT1 is a key regulator of immune response. Myeloid-specific PRMT1 knockout mice are hyperresponsive to LPS and deficient in PPARγ-dependent macrophage M2 polarization. We aimed to define the role of myeloid PRMT1 in alcohol-associated liver tumor progression using a mouse model of DEN injection followed by Lieber–DeCarli alcohol liquid diet feeding. We found that PRMT1 knockout mice showed significantly lower expression of IL-10 and IL-6 cytokines in the liver and downstream STAT3 activation, which correlated with reduced number of surface tumors, reduced proliferation, and reduced number of M2 macrophages in the liver as well as within proliferating nodules. We found that blocking IL-6 signaling in alcohol-fed mice reduced the number of tumors and liver proliferation in wild-type mice but not in knockout mice suggesting that reduced IL-6 in PRMT1 knockout mice contributes to the protection from alcohol. Additionally, PRMT1 knockout did not show any protection in tumor formation in the absence of alcohol. Finally, we confirmed that this mechanism is relevant in humans. We found that PRMT1 expression in tumor-associated macrophages correlated with STAT3 activation in human HCC specimens. Taken together, these data suggest that the PRMT1–IL-6–STAT3 axis is an important mechanism of alcohol-associated tumor progression.